The content of matrix metalloproteinase-1, -9 and tissue inhibitor of matrix metalloproteinase-1 in patients with bronchial asthma and obesity - V. V. Kachkovska; L. N. Prystupa (Zaporozhye State Medical University, 2023)
Airway remodeling is a significant factor in the progression of respiratory failure in bronchial asthma (BA). Obesity can contribute to inflammation, and consequently - airway remodeling, by increased production of matrix proteinase (MMP). However, the mechanisms of remodeling in different phenotypes of BA, especially in comorbid patients, remain poorly understood. The aim of the research was to examine the levels of remodeling markers MMP-1, MMP-9 and tissue inhibitor of matrix proteinases (TIMP-1) in obese asthmatic patients, taking into account their age at the onset of BA, the severity of symptoms and the level of control. Material and methods. 195 patients with BA associated with obesity were examined. The control group consisted of 95 practically healthy people. Patients were divided into two groups: Group I included 100 patients with early onset, and Group II included 95 patients with late onset of BA. The study was approved by the Bioethics Commission of the Medical Institute of Sumy State University. Statistical analysis of the obtained results was carried out using the SPSS-17 program. Results. The content of MMP-1, -9 and TIMP-1 was higher in patients with early (129.40 ± 7.86; 177.30 ± 9.19; 142.40 ± 12.22 ng/ml, respectively) and late (196.60 ± 9.62; 289.80 ± 16.23; 187.50 ± 11.34 ng/ml, respectively) BA with obesity compared to practically healthy individuals (р < 0.005). Patients with late-onset BA associated with obesity likely had higher indicators than those with early BA. In patients with early BA, the levels of MMP-1, -9, and TIMP-1 were not significantly different depending on the severity of the disease (р > 0.05). However, in patients with severe late BA, the levels of these markers were higher compared to those with mild BA (р < 0.05). Levels of MMP-1 and MMP-9 in patients with early-onset and late-onset BA with obesity were higher in the absence of disease control compared to those in complete and partial control, but in late-onset exceeded those in early-onset. Conclusions. Considering the obtained results, it can be assumed that the level of MMP-1, MMP-9 and TIMP-1 in obese patients with BA can serve as biomarkers of airway remodeling, namely, the severity and the level of BA control.